Deteksi Karsinoma Nasofaring Mengunakan Rapid Test Uji Imunokromatografi pada Petugas SPBU - Roni Afriansya; Umi Rosidah; Eko Naning Sofyanita (Jaringan Laboratorium Medis, 2023)
Nasopharyngeal cancer (NPC) is the 4th most common malignancy in Indonesia, after breast, cervical and lung cancer. The risk factors for this cancer are Epstein-Barr virus, gender, race, adult age 30-50 years, family history, drinking alcohol and smoking. The prevalence of NPC in Indonesia is 6.2/100,000, with nearly 13,000 new cases, but this is a small proportion that has been documented. Adham et al (2012) reported that NPC is the most common head and neck cancer (28.4%), with a male-female ratio of 2:4 and is endemic to the island of Java. The existence of knowledge about NPC starting from prevention, early detection, appropriate treatment will be able to help overcome problems caused by nasopharyngeal cancer. Early detection is very important. If NPC is found at an early stage, the cure rate is quite high, reaching 90%. The purpose of this study was to find out whether there were gas station workers in Semarang City who experienced NPC. This study used an analytic survey method with a cross-sectional approach. The results of the study of 20 Semarang City Gas Station officers found that the characteristics based on age were the most in the range 31-50, namely 70%. Characteristics based on gender of the 20 gas station attendants are all male (100%). Characteristics based on length of service are 1 - 10 years (35%), 11 - 20 years (35%) and 21 - 30 years (30%) respectively. Characteristics based on smoking history, 55% of respondents smoked and 45% did not smoke. And the NPC examination results of all respondents (100%) were NPC negative.